Snyder Space-Time: K-Loop and Lie Triple System - Girelli, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
Different deformations of the Poincaré symmetries have been identified for various non-commutative spaces (e.g. κ-Minkowski, sl(2,R), Moyal). We present here the deformation of the Poincaré symmetries related to Snyder space-time. The notions of smooth ''K-loop'', a non-associative generalization of Abelian Lie groups, and its infinitesimal counterpart given by the Lie triple system are the key objects in the construction.